Konsep Pengelolaan Desain Lingkungan Pendidikan Anak Usia Dini - Ijar Salna; Lu’lu Rahmadanti; Nur Saadah (Institut Nalanda, 2024)
A conducive learning atmosphere or environment will affect the child's learning and teaching process. A conducive learning environment tends to encourage children to learn calmly and concentrate. This research method utilizes literature by looking for theoretical references that are relevant to existing cases and problems. The results of this study indicate that; (1) The concept of managing a preschool educational environment: an environment that encourages and helps children explore and experiment, Optimizing meaningful objects and play equipment (2) in indoor and outdoor activities must pay attention to the Utilization of the PAUD environment in indoor and outdoor spatial planning. for example, an indoor learning environment Make sure to pay attention to the child's freedom of movement and the outdoor learning environment must pay attention to a very enjoyable learning environment for children. Outdoors give children more freedom to move because the outdoors are very conducive to the development of children's gross motor skill